Pelatihan Pembuatan Nutrisi Sehat dan Menarik sebagai Bekal Anak Sekolah - Nora Wulandari; Vivi Anggia; Tuti Wiyati (Jurnal Pengabdian Pada Masyarakat, 2019)
TRAINING ON MAKING HEALTHY AND ATTRACTIVE NUTRITION AS FOOD FOR CHILDREN IN SCHOOL. This community service program was motivated by hazardous food found in schools in the DKI Jakarta area. The purpose of this community service activity was as an effort to promote health in realizing the community, especially the healthy of young people by making it a habit to consume snacks or healthy foods that are unique and attractive in the form of bento. The community service was carried out by means of socialization and counseling followed by a direct demonstration of making bento to the target audience, namely the students' parents and the Al-Hikma Kindergarten school committee Perumnas Klender, East Jakarta. This activity showed a positive response from the participants which was shown from the enthusiastic participants' devotion in participating in the activities as well as being potential entrepreneurs in schools in the East Jakarta area. The outputs obtained from this activity were: a) creation of community understanding, especially housewives on the importance of healthy nutrition for children, b) increasing community creativity in making attractive healthy food as provisions for school children, c) entrepreneurial opportunities for housewives which can increase community income.